pengaruh customer trust, customer satisfaction, ability dan benevolance terhadap customer loyalty di restoran cepat saji mc donald's ambarukmo di yogyakarta - ach sari aprili sabtu (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study ains to : know the significant influence of satisfaction positive influence on consumer loyalty; know the significant effect of trust positive influence on consumer loyalty; know the significant influence of ability positive influence on consumer loyalty; know the significant effect of benevolence positive influence on consumer loyalty. research location in Yogyakarta. The research poulasi is a customer living in Yogyakarta. Samples of 100 respondents were taken using accidental sampling technique of data collection method using koesioner. data analysis used is descriptive analysis, and multiple regression analysis. The results of this study indicate that consumer ability significantly influence consumer loyalty; consumer satisfaction has significant effect on consumer loyalty; consumer benevolance significantly affects consumer loyalty; consumer trust has significant effect on consumer loyalty.